UPAYA BLACK LIVES MATTER GLOBAL NETWORK FOUNDATION DALAM MERESPON RASISME DI INGGRIS - ', Reihan; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Black Lives Matter Global Network Foundation is an organization that rejects violence against the black race and was formed based on the movement of the same name, namely Black Lives Matter. In 2020, this movement went global after the death of George Floyd at the hands of a police officer. UK was one of the countries that sympathized with this event took part in the Black Lives Matter movement. For the black community there, even though they do not have similar cases, racism is a problem they often face as a minority. This research aims to analyze the efforts of the Black Lives Matter Global Network Foundation to addres the racism in the UK. This research uses Global Civil Society theory and group level analysis to examine the changes created by the BLMGNF organization. Global Civil Society theory itself is a theory that focuses on the shared ideas that a group share and how would they realize that idea and how organizations could impact the global social environment. This research shows that the role and efforts of BLMGNF are able to reduce the amount of racism against black people in the UK. BLMGNF and others black community help shift the norm of the UK society to be a better one, where the donation given to anti-racism groups to accommodate black community in getting employment opportunity. Keywords: Black Lives Matter, BLMGNF, UK, Racism.